Reviving a Classic Antigen with a Cutting-Edge Approach: Nanobodies for HER2+ Breast Cancer - Chiara Castrignano; Federica Di Scipio; Francesco Franco; Barbara Mognetti; Giovanni Nicolao Berta (MDPI AG, 2023)
The serendipitous discovery of nanobodies (NBs) around two decades ago opened the door to new possibilities for innovative strategies, particularly in cancer treatment. These antigen-binding fragments are derived from heavy-chain-only antibodies naturally found in the serum of camelids and sharks. NBs are an appealing agent for the progress of innovative therapeutic strategies because they combine the advantageous assets of smaller molecules and conventional monoclonal antibodies (mAbs). Moreover, the possibility to produce NBs using bacterial systems reduces manufacturing expenses and speeds up the production process, making them a feasible option for the development of new bio-drugs. Several NBs have been developed over the past 10 years and are currently being tested in clinical trials for various human targets. Here, we provide an overview of the notable structural and biochemical characteristics of NBs, particularly in their application against HER2, an extracellular receptor that often gets aberrantly activated during breast cancer tumorigenesis. The focus is on the recent advancements in diagnostic and therapeutic research up to the present date.